What does it say and who said it? The contingent effects of online word of mouth in China. Issue 4 (7th November 2016) - Luo, Biao; Zhang, Zheyu; Liu, Yong; Gao, Weihe
Abstract : Purpose: The purpose of this paper is to examine how consumers respond to online word of mouth (WOM) with different valence (i.e. what does it say) and from different sources (i.e. who said it) in an important emerging economy, China. Design/methodology/approach: Theory with experiments. Findings: The authors find that Chinese consumers seek confirmatory information and pay greater attention to WOM that agrees with their initial attitude. Consumers with a high (vs low) need for cognition are more likely to rate WOM from far (vs closer) social distance as more impactful on themselves. For public-consumption products, the consumers are influenced more by "who said it" (source) than by "what does it say" (valence). The reverse holds for private consumption. Research limitations/implications: The paper could be extended to other online behaviors. It can also be extended to empirical testing using market data. Practical implications: Since Chinese consumers tend to focus on online information that is consistent with their initial attitude, it can be more difficult for either the seller or third-party website to utilize online WOM as a persuasive tool in China than in other countries. Firms may also customize their online strategies based on product category. For products that are consumed in private, WOM content is more important than source. If the firm wants to facilitate consumer interaction and influence, greater attention should be paid to make the content easy to access and utilize. Social implications: Due to the explosive growth of e-Commerce in China, many global and Chinese firms rushed to set up online communities to facilitate information exchange among consumers. Our findings indicate that the impact of these communities may have been overvalued. Chinese consumers are influenced by online information, but if the majority of the online messages are from anonymous strangers, consumers tend to discount their credibility. Originality/value: Our study represents an earlier effort to predict, and test, how online WOM can be associated with the specific cultural and market environments. It provides direct implications for both consumer behavior and firm strategy.